The logic of revocation of mandate and the game of indeterminacy - Olmos de la Torre, Francisco Alejandro (2023)
This paper refutes the arguments that led Mexican constitutional court not to invalidate the question and answers that were the object of the revocation of mandate mechanism in that country. It accepts the premise about the constitutional intention of not creating a consultation on the ratification of the mandate; likewise, based on a logical investigation on the implications of considering «revocation» and «ratification» as two contrary concepts, it tries to demonstrate that giving the people a choice only between revoking and not revoking, due to the indeterminacy that the latter option casts on the trust in politicians, is what comes closest to the constitutional model to exercise the right to express an opinion on the matter.